New evidence on financing equity in China's health care reform - A case study on Gansu province, China - Chen Mingsheng; Chen Wen; Zhao Yuxin (BMC, 2012)
Abstract Background In the transition from a planned economy to a market-oriented economy, China's state funding for health care declined and traditional coverage plans collapsed, leaving China's poor exposed to potentially ruinous health care costs. In reforming health care for the 21st century, equity in health care financing has become a major policy goal. To assess progress towards this goal, this paper examines the equity characteristics of health care financing in a province of northwestern China, comparing the equity performance between urban and rural areas at two different points in time. Methods Analysis of whether health care financing contributions were progressive according to income were made using the Kakwani index for each of the four health care financing channels of general taxes, public and private health insurance, and out-of-pocket payments. Two rounds of surveys were conducted, the first in 2003 (13,619 individuals in 3946 households) and the second in 2008 (12,973 individuals in 3958 households). Household socio-economic, health care payment, and utilization information were recorded in household interviews. Results Low-income households have undertaken a larger share of the health care financing burden in recent years, reflected by negative Kakwani indices, which indicate a regressive system. We found that the indices for general taxation were −0.0024 (urban) and −0.0281 (rural) in 2002, and −0.0177 (urban) and −0.0097 (rural) in 2007. Public health insurance presented different financing distributions in urban and rural areas (urban: 0.0742 in 2002, 0.0661 in 2007; rural: -0.0615 in 2002,0.1436 in 2007.). Out-of-pocket payments were progressive but not equitable. Public health insurance coverage has expanded but financing equity has decreased. Conclusions Health care financing policies in China need ongoing reform. Given the inequity of general consumption taxes, elimination of these would improve financing equity considerably. Optimizing benefit packages in public health insurance is as important as expanding coverage, both for health care financing and for utilization management as well. Although they are progressive, out-of-pocket payments are not equitable in China and have the effect of excluding the poor from health care as they cannot afford to pay for medical care and so withdraw from treatment.